The Application of Time Token Learning Technique in Improving Students' Sociology Learning Activities - Arfenti Amir; Muh. Reski Salemuddin; Akhiruddin; Sriwahyuni; Jalal; Abdul. Malik Iskandar (CV. Eureka Murakabi Abadi, 2022)
This study aimed to determine the increase in sociological learning activities of students by applying the Time Token type Cooperative learning technique, this type of research used classroom action research (CAR), the subject of this research was class XI Social Science 1 students of SMA Negeri 10 Makassar, The total numbers of students were 29 students. Data were obtained through observation sheets of students’ activities during group work presentations from cycle I to cycle II, data analysis was carried out using scores based on reference assessments. Data shows that there is an increase in student learning activities after applying the Time Token Cooperative learning model. In class XI Ips1 students at SMA Negeri 10 Makassar, in cycle I 78.6 and cycle II 82.7. The conclusion of this study is that by applying the Cooperative Learning model of Time Token type, it can increase the sociology learning activities of students in class XI IPS 1 SMA Negeri 10 Makassar.